The Influence of Accountability and Transparency on the Quality of Financial Reports with the Internal Control System as a Moderating Variable (Empirical Study at the Buru Regency KPU) - Tiara Dwi Cahyani Yunus; Jefry Gasperz; Dwi Haryanti (LP2M IAIN Palopo, 2026)
This study aims to analyze the influence of accountability and transparency on the quality of financial reports with the internal control system as a moderating variable at the General Election Commission (KPU) of Buru Regency. This type of research is quantitative research with primary data sources obtained through the distribution of questionnaires to all 40 employees of the KPU of Buru Regency. The sampling technique used total sampling. The data analysis method used Partial Least Square (PLS) with the help of SmartPLS. The results show that accountability and transparency have a positive and significant effect on the quality of financial reports. However, the internal control system does not moderate the influence of accountability or transparency on the quality of financial reports.